Search for dark matter candidates and large extra dimensions in events with a photon and missing transverse momentum in pp collision data at sqrt[s]=7 TeV with the ATLAS detector. - Aad, G; Abajyan, T; Abbott, B; Abdallah, J; Abdel Khalek, S; Abdelalim, A; Abdinov, O; Aben, R; Abi, B; Abolins, M; Abouzeid, O; Abramowicz, H; et al. (2013)
Results of a search for new phenomena in events with an energetic photon and large missing transverse momentum in proton-proton collisions at sqrt[s] = 7 TeV are reported. Data collected by the ATLAS experiment at the LHC corresponding to an integrated luminosity of 4.6 fb(-1) are used. Good agreement is observed between the data and the standard model predictions. The results are translated into exclusion limits on models with large extra spatial dimensions and on pair production of weakly interacting dark matter candidates.